Integral (1/(x^2 - 9))dx
To solve this, we have to use trigonometric substitution. I'm going to use "t" instead of theta, though on paper I would normally use theta.
Let x = 3sec(t)
dx = 3sec(t)tan(t)dt
After the substitution, we have
Integral { ( 1 / [9sec^2(t) - 9] ) (3sec(t)tan(t)) } dt
Simplifying, we have
Integral ( [3sec(t)tan(t)] / [9sec^2(t) - 9] ) dt
Factoring out a 9 from the bottom, we have
Integral ( [3sec(t)tan(t)] / [9(sec^2(t) - 1)] )dt
By the identity "tan squared equals secant squared minus one",
Integral ( [3sec(t)tan(t)] / [9tan^2(t)] ) dt
Note that the 3 on the top will cancel out from the 9 in the bottom, leaving us with
Integral ( [sec(t)tan(t)] / [3tan^2(t)] ) dt
Let's pull out that 3 in the denominator. We would get a (1/3) outside of the integral as a result.
(1/3) * Integral ( [sec(t)tan(t)] / [tan^2(t)] ) dt
Note that the tan(t) on the numerator will cancel with the tan term in the denominator.
(1/3) * Integral ( [sec(t)]/[tan(t)] ) dt
Now, let's change everything to sines and cosines.
(1/3) * Integral ( [1/cos(t)] / [sin(t)/cos(t)] ) dt
Multiply the top and bottom by cos(t), we have
(1/3) * Integral ( 1/sin(t) ) dt
By definition,
(1/3) * Integral (csc(t)) dt
The integral of csc(t) is not something obvious, but definitely something one *needs* to know. The answer is
ln |csc(t) - cot(t)|.
(1/3) * ln |csc(t) - cot(t) | + C
At this point, we need to get the x variable in the solution.
Note that earlier, we assigned x = 3sec(t). From here, it follows that sec(t) = x/3
Remember SOHCAHTOA? Since cos(t) = adj/hyp, it follows that secant, which is the reciprocal of cosine, is hyp/adj.
Therefore, from sec(t) = x/3, construct a right angle triangle with angle t, and hypotenuse equal to x, adjacent equal to 3. It follows that the remaining side, the opposite, will be sqrt(x^2 - 9).
hyp = x
adj = 3
opp = sqrt(x^2 - 9)
(1/3) * ln |csc(t) - cot(t) | + C
csc(t) = hyp/opp = x/3
cot(t) = adj/opp = 3/sqrt(x^2 - 9), so our answer is
(1/3) * ln |x/3 - 3/sqrt(x^2 - 9)| + C
2007-01-16 21:13:01
·
answer #1
·
answered by Puggy 7
·
0⤊
0⤋
First graph the triangle and see: the base is 2 and height is 9 a) The formula for the area is (base)(height)/2 = 2*9/9 = 9 b)Other way is: find the equation of the line using the points (1,0) and(3,9)... it is y = (9/2)(x-1) Now use the integral: area = integral(from 1 to 3) of the function (9/2)(x-1) The integral of (9/2)(x-1) is (9/2)(x^2/2 - x) ... from 1 to 3.... the result is 9 OK!
2016-03-29 01:18:02
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
You should discompose the integrand in simple fraction1/(x^2-9)= a/(x-3)+b/(x+3) For calculating a and b you can put:
1= a*(x+3 )+ b*(x-3) so a=1/6 and b=-1/6 so 1/(x^2-9) =
1/6* (1/(x+3) -1/(x-3) )
Integrating each summand you get 1/6 (logIx+3I - logIx-3I) which can be written as
logI(x+3)/(x-3)I^1/6 log means" e "based logs
2007-01-16 23:47:06
·
answer #3
·
answered by santmann2002 7
·
0⤊
0⤋